Striatum supports fast learning but not memory recall - Kimberly Reinhold; Marci Iadarola; Shi Tang; Annabel Chang; Whitney Kuwamoto; Madeline A. Albanese; Senmiao Sun; Richard Hakim; Joshua Zimmer; Wengang Wang; Bernardo L. Sabatini (Nature, 2025)
Abstract Animals learn to carry out motor actions in specific sensory contexts to achieve goals. The striatum has been implicated in producing sensory–motor associations 1 , yet its contributions to memory formation and recall are not clear. Here, to investigate the contribution of the striatum to these processes, mice were taught to associate a cue, consisting of optogenetic activation of striatum-projecting neurons in visual cortex, with the availability of a food pellet that could be retrieved by forelimb reaching. As necessary to direct learning, striatal neural activity encoded both the sensory context and the outcome of reaching. With training, the rate of cued reaching increased, but brief optogenetic inhibition of striatal activity arrested learning and prevented trial-to-trial improvements in performance. However, the same manipulation did not affect performance improvements already consolidated into short-term (less than 1 h) or long-term (days) memories. Hence, striatal activity is necessary for trial-to-trial improvements in performance, leading to plasticity in other brain areas that mediate memory recall.